Biology and Pathogenesis of B Non-Hodgkin Lymphoma in Childhood: a Review - Klumb, Claudete Esteves (2001)
The non-Hodgkin’s lymphoma in childhood encompasses a closely related group of aggressive Bcell tumors that includes Burkitt’s and non Burkitt’s lymphomas among other less frequent types. Burkitt’s lymphoma includes two distinct forms, namely the endemic and sporadic types, which are characterized by the presence of a chromosomal translocation leading to c-myc proto-oncogene deregulation. Although the normal function of c-myc remains enigmatic, recent data indicate that it has a central role in several fundamental aspects of cellular biology, including proliferation, differentiation, metabolism, and apoptosis. This review focuses on the clinical, epidemiological and molecular features of B non-Hodgkin’s in childhood and discusses new insights into molecular mechanisms of c-myc activation associated to p53 and Rb gene mutations with Burkitt’s lymphoma pathogenesis. The role of EBV virus infection and its potential relevance to virus-induced carcinogenesis and the interaction of viral factors with cellular tumor supressor proteins is also discussed.